Pemphigus vulgaris and its clinical manifestations: case report - de-Sousa, Alayde Ramos; Silva, Walleska Gomes Moreno; Cândido-Soares, Lara Eunice; da-Silva, Alexandre Monteiro; Leite, Arthur Gomes (Journal of Oral Diagnosis, 2020)
Autoimmune diseases have been steadily increasing in recent decades. The antibodies produced interact with the tissue itself resulting in the formation of blisters that affect the skin and mucous membranes, called vesicle-bullous autoimmune pathologies, one of the most common being pemphigus vulgaris. Therefore, it is characterized as a chronic and rare disease, with cutaneous and oral manifestations. The lesions are characterized by the formation of blisters that break easily and give place to extensive ulcerations. Thus, it is necessary to know about the main cutaneous and oral clinical manifestations, as well as the clinical evolution of the disease so that an early diagnosis can be made, which can lead to successful treatment. The objective of this study is to present a clinical case of a patient diagnosed with pemphigus vulgaris and its clinical dermatological and oral ma- nifestations at the beginning of the disease, as well as during the treatment confirmed by biopsy, histopathological examination, direct immunofluorescence and clinical findings. For data collection, questionnaires, intraoral and extraoral photographs of the face, armpits, chest, groin and genital mucosa were used. It was concluded that pemphigus vulgaris is a disease characterized by the formation of erythematous blisters and ulcers, which can reach any oral location. On the skin, the lesions progress rapidly in erosion and crusting formation, showing a symmetrical predilection for the chest, groin, armpits, scalp and face.